Geoelectrical model of Strumica valley– Bansko spa - Doneva, Blagica (Geologica Macedonica, 2015)
Geoelectrics is a branch of geophysics which studies and monitors electrical and, along with geomagnetism, electromagnetic fields of the Earth. Possibility for application of geoelectrical explorations is based on the fact that minerals, that composed the rock complex, have different electrical, and partially magnetic characteristics. Electrical methods study natural and artificial electrical flows in the Earth and give data for distribution of the rocks with different electrical features. Geoelectrical mapping and sounding represent two basic methods of geoelectrical research of Earth interior structure. Using geoelectrical mapping, as a part of this method, is measured specific electrical resistance along the profile, with constant distance between the probes or constant depth of exploration. This paper will present process of geoelectrical measurements of Strumica valley or terrain around Bansko spa. Described is procedure of measurement, data processing, the obtained models and profiles of the terrain and the correlation between the models and the geological structure. Modern computer systems and programs (software) enable processing of large amounts of data in a relatively short time and models can also be with many parameters. The paper is based on data from field measurements.